A‐Site Cation Engineering in 2D Ruddlesden–Popper (BA)2(MA1‐xAx)2Pb3I10 Perovskite Films. Issue 18 (7th March 2021) - Ramos‐Terrón, Susana; Verdugo‐Escamilla, Cristóbal; Camacho, Luis; de Miguel, Gustavo
Abstract: The partial incorporation of large organic cations into the octahedral sites of 3D perovskites has been widely investigated but few works have reported their addition in 2D Ruddlesden–Popper (RP) perovskites. Here, the gradual substitution of the methylammonium (MA) cation in thin films of 2D RP perovskites (BA)2 (MA)2 Pb3 I10 (BA = n ‐butylammonium) by guanidinium (Gua), dimethylammonium (DA), ethylammonium (EA), rubidium (Rb), propylammonium (PA), cesium (Cs) or formamidinium (FA) to synthesize mixed A‐cation (BA)2 (MA1‐ x A x )2 Pb3 I10 perovskites has been studied. The limit in the percentage of the A‐site cation at which it is homogeneously incorporated in all n phases without destabilizing the overall structure is determined. It is found that the structural changes in the 2D RP perovskites may lead to modifications of the optoelectronic properties as larger bandgap (EA), blue‐shift of the PL peak position (above the threshold), strong quenching of the PL (Cs) or reduced concentration of trap states (Gua and EA). Solar devices fabricated with the different mixed A‐cation 2D RP display an enhanced performance for those perovskites containing low percentages of Gua or EA cations. This characterization is very valuable to correlate the size and shape of the A‐cation with the changes of the properties of the material. Abstract : A‐site cation engineering in 3D perovskites has been widely investigated to optimize the performance of solar devices. Here, the gradual substitution of the methylammonium (MA) cation in thin films of 2D Ruddlesden–Popper perovskites by seven types of cations is studied, finding a good correlation between the size of the A‐cation and the changes of the optoelectronic properties.